Fundación el Repique, una apuesta de la maestra Gladys González Fernández. Relato autobiográfico. (2021)
From the methodological point of view, this presentation is the result of correlational qualitative research, and in a mixed approach that collects information from testimonies and stories of people who were and are part of the transfer of life history as artist, trainer and manager of Gladys Argenis González. It tells how she managed to fulfill goals, dreams and how day by day she continues to work in order to leave a legacy forever, intending that she be remembered by future generations, with respect for doing cultural as an artist, trainer and manager with the firm purpose that this story serves as a guide, example and inspiration mainly for children and young people who wish to dabble in dance as an art.